Cognitive and behavioral processes predict anxiety and depression in patients with pulmonary hypertension. (14th December 2022) - Rawlings, Gregg H.; Thompson, Andrew R.; Armstrong, Iain; Novakova, Barbora; Beail, Nigel
Abstract: Emotional and psychological difficulties cannot fully be explained by disease‐related factors in people with pulmonary hypertension (PH). This study examined the relationship between anxiety, depression, demographic, objective and subjective PH factors, and self‐reported cognitive and behavioral processes, which have been associated with mood in clinical and nonclinical samples. This is a secondary analysis of baseline data from 77 adults with PH who took part in a randomized controlled trial of a self‐help intervention targeting anxiety in PH. Participants completed self‐report measures including: demographic (age, gender, ethnicity, education, employment) and clinical questionnaire (PH diagnosis, functional class, years since diagnosis), depression (PHQ‐9), anxiety (GAD‐7), health‐related quality of life (emPHAsis‐10), dyspnea (D12), and cognitive and behavioral processes (CBP‐Q) scale. Data were analyzed using correlational and regression analyses. Overall, 70% and 63% of participants scored above the clinical cut off for anxiety and depression, respectively. Demographics were not associated with anxiety or depression. PH‐related factors were correlated with depression but not anxiety. A multiple regression analysis suggested dyspnea and cognitive processes significantly predicted anxiety whereas behavioral processes were not a unique predictor. In contrast, dyspnea and behavioral processes predicted depression whereas cognitive processes did not. While a body of evidence exists demonstrating people with PH are more likely to experience anxiety and depression, less is known about factors that cause and maintain these disorders. Findings highlight the significance of subjective factors that could be a target for screening and psychological treatments for emotional difficulties, such as cognitive behavioral therapy.